PENGUJIAN PENANDA RANDOM AMPLIFIED POLYMORPHISM DNA UNTUK MENGETAHUI KESTABILAN GENETIK KLON JATI (Tectona grandis) - ILG Nurtjahjaningsih; Toni Herawan; Reza Permatasari Rachma; Anto Rimbawanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2018)
This study aimed to test RAPD markers to assess genetic stability of teak clones. Two experimental steps were carried out. First, nine RAPD markers were screened to verify the level of polymorphic loci; second, the polymorphic loci were applied to test genetic stability of clones. To test polymorphism levels of the primers, DNA was isolated from eight leaf samples that were collected from a seed orchard located at Watusipat, Gunung Kidul. To verify genetic stability of clones, DNA was isolated from leaf samples of 24 ramets of 3 clones after second sub-culturing. Results showed that amplification of 5 out of 9 RAPD primers were be consisten and produced 12 polymorphic loci. The number of polymorphic alleles per locus ranged between 1 and 3; the allele sizes were between 400 and 1,050 base pairs (bps). The percentage of polymorphic loci was 100%; it meant that overall loci have high polymorphism level. Based on these loci showed that the 24 ramets are clones; there was no somaclonal variation or high genetic stability. However, these loci need to be validated using more stable DNA markers.